THE EFFECT OF ADVERTISING ON ONLINE SITES AND LIFESTYLE IN THE ERA OF DIGITAL ON REPURCHASING INTEREST - Tang, Sefnat Aristarkus; Maro, Yustina (International Journal of Multidisciplinary Research and Literature, 2022)
Interest is a consumer's desire and action to repurchase a product due to the satisfaction received after receiving what they desire from a product. This study aims to determine the effect of advertising on online sites and lifestyle in the digital era on interest in repurchasing at online stores for Educators and Education Personnel at Tribuana Kalabahi University, Alor Regency. Data was collected using a questionnaire, while the data analysis technique used multiple linear regression. The results showed that partially advertising on online sites positively affected repurchase interest at online stores, partly lifestyle. The digital era has a positive and significant impact on repurchase interest in online stores; Simultaneously, advertisements on online sites and lifestyles in the digital age positively affect repurchase interest at online stores. The Adjusted R Square value of 0.428 or 42.8% means that buying interest in online stores is influenced by advertisements on online sites and lifestyles in the digital era by 42.8% the remaining 57.2% this affected by other variables not examined in this study this research.